The Use Of Pragmatic Approach to Enhance Students’ Speaking Skills at MA Samsyul Huda Tegallinggah - Alfillail, Nur; Putra, I Nyoman Adi Jaya; Dewi, Kadek Sintya (STKIP AGAMA HINDU SINGARAJA, 2024)
This research aimed to analyze the use of pragmatic approach to enhance students' speaking skills at MA Syamsul Huda Tegallinggah.The focus of this study was on the learning activities of 25 students in class XI B and their speaking test results.Data were collected through various techniques, including observation, interviews, and the assessment of speaking skill test results.The research design used in this study was Classroom Action Research, consisting of two cycles, Cycle I and Cycle II. Based on the results of the action implementation in both cycles, it was found that the pragmatic approach increased student participation in learning. Additionally, it proved to be effective in improving students' speaking skills. In Cycle I, students achieved an average score of 75.52 with a pass rate of 64%, where 19 out of 25 students were declared successful. Meanwhile, in Cycle II, the average score increased to 79.04 with a pass percentage of 84%. In fact, before the implementation, only 14 students or 56% of them were declared successful. The emphasis of the pragmatic approach in this research was on providing opportunities for students to practice using English in its contextual usage. Thus, in the learning process, students not only focused on theory but also engaged in practical language application.